Orientasi Baru Pendidikan Islam Era Millenial - Lestari, Indah; Misbah, Muhammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This paper examines the main orientation of education which is not only a mastery of knowledge, but as a bridge that leads people to awareness, belief and positive thoughts so that they can know God better as part of the existence of life in this world. The method used is library research method with a descriptive normative approach that emphasizes the analysis of the data sources found. The results of the analysis of verses and data sources can be concluded that the purpose of Islamic education is to shape humans according to their nature so that they can live like human beings in terms of strengthening faith, reason, physical, spiritual and social oriented to piety as servants of Allah and caliphs in the world. As humans, there needs to be a balance between human abilities in terms of intelligence, religious, professional, and social. In addition, the orientation of Islamic education can be packaged with economic stability in order to eradicate inequality and social injustice. Educational institutions have a special task and role to produce people who think and feel, think and do remembrance, and people who are humble are not arrogant.